2022
DOI: 10.3389/fphar.2022.913420
|View full text |Cite
|
Sign up to set email alerts
|

Based on Network Pharmacology and Gut Microbiota Analysis to Investigate the Mechanism of the Laxative Effect of Pterostilbene on Loperamide-Induced Slow Transit Constipation in Mice

Abstract: Background: Pterostilbene (PTE) is a natural polyphenol compound that has been proven to improve intestinal inflammation, but its laxative effect on slow transit constipation (STC) has never been studied. This study aims to investigate the laxative effect of PTE on loperamide (LOP)-induced STC mice and its influence on intestinal microbes through a combination of network pharmacological analysis and experimental verification.Material and Methods: PTE was used to treat LOP-exposed mice, and the laxative effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Gut microbiota are closely related to host health and influenced by nutritional intake and lifestyle . Previous studies have shown that prebiotics can reduce constipation by regulating the microbial composition of the intestinal tract. , Both polyphenols and polysaccharides extracted from FBT have been proven to regulate intestinal flora and maintain host health. , FTE is extracted from FBT infusion, which has been proven to promote the colonization of beneficial bacteria such as Roseburia and Lactobacillus . Here, the 16S rRNA gene amplicon sequencing technology was used to analyze gut microbial changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gut microbiota are closely related to host health and influenced by nutritional intake and lifestyle . Previous studies have shown that prebiotics can reduce constipation by regulating the microbial composition of the intestinal tract. , Both polyphenols and polysaccharides extracted from FBT have been proven to regulate intestinal flora and maintain host health. , FTE is extracted from FBT infusion, which has been proven to promote the colonization of beneficial bacteria such as Roseburia and Lactobacillus . Here, the 16S rRNA gene amplicon sequencing technology was used to analyze gut microbial changes.…”
Section: Discussionmentioning
confidence: 99%
“…52 Previous studies have shown that prebiotics can reduce constipation by regulating the microbial composition of the intestinal tract. 53,54 Both polyphenols and polysaccharides extracted from FBT have been proven to regulate intestinal flora and maintain host health. 25,26 FTE is extracted from FBT infusion, which has been proven to promote the colonization of beneficial bacteria such as Roseburia and Lactobacillus.…”
Section: ■ Discussionmentioning
confidence: 99%
“…63 PT can also improve intestinal inflammation and motility disorders, promoting the richness and diversity of probiotics. 64 Our past research has shown that PT effectively increases the relative abundance of Bacteroidetes and decreases the relative abundance of Firmicutes. 65 Recently, PT has been reported to reduce inflammation and alter the gut microbiota in rheumatoid arthritis.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Polyphenol compounds such as resveratrol and PT are recommended as dietary additions due to their antiobesity effect . PT can also improve intestinal inflammation and motility disorders, promoting the richness and diversity of probiotics . Our past research has shown that PT effectively increases the relative abundance of Bacteroidetes and decreases the relative abundance of Firmicutes .…”
Section: Discussionmentioning
confidence: 99%
“…In the past decades, as a neurodegenerative disease, the incidence of AD has increased year by year, threatening more and more elderly population ( Li et al, 2021 ; Yao et al, 2022 ). As a natural medicine, AOF contains a variety of components and has the advantage of multiple targets, which also brings great challenges to researchers ( Zuo et al, 2021 ; Peng et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%